Implementasi Value Engineering (VE) Pada Proyek Jalan Oleh Konsultan Dan Kontraktor - Sugiono Sugiono; Setya Winarno (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
The application of VE in the construction sector is a systematic process by a multidisciplinary team focused on value and function. The adoption of EV in construction projects offers the potential for significant savings on project budgets. Seeing the current economic conditions, in the construction of ongoing works that require a sizable capital allocation, it is necessary to reconsider whether the design used is appropriate or not optimal. Among the many statements regarding the success factors of VE implementation in Indonesian construction, the knowledge and experience of VE of the construction parties is a key success factor as stated by the consultant and provided by the contractor.